2010
DOI: 10.1183/09031936.00153509
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to volatile organic compounds and loss of pulmonary function in the elderly

Abstract: Volatile organic compounds (VOCs) are reported to cause adverse effects on pulmonary function in occupationally exposed workers. However, evidence is lacking on the effect in the general population. We hypothesised that VOCs impair pulmonary function through enhancing oxidative stress, especially in the elderly population.A longitudinal panel study of 154 elderly people was performed in South Korea. Repeated spirometric tests were performed up to eight times on different days for each subject. We also measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 33 publications
3
61
0
1
Order By: Relevance
“…A recent study suggested that formaldehyde levels were associated with increased risk of reporting COPD in elderly nursing home residents (74), and few studies have suggested that exposure to aldehydes and volatile organic compounds (VOCs) may be linked to respiratory symptoms and lung function in the elderly (79); however, the role of aldehydes and VOCs in COPD, to our knowledge, has not been studied.…”
Section: Indoor Air Pollution and Copdmentioning
confidence: 99%
“…A recent study suggested that formaldehyde levels were associated with increased risk of reporting COPD in elderly nursing home residents (74), and few studies have suggested that exposure to aldehydes and volatile organic compounds (VOCs) may be linked to respiratory symptoms and lung function in the elderly (79); however, the role of aldehydes and VOCs in COPD, to our knowledge, has not been studied.…”
Section: Indoor Air Pollution and Copdmentioning
confidence: 99%
“…Desktop sized 3D printers in particular, are often used in educational institutions, public spaces such as libraries, design offices and within homes (Harrop 2015). It is known that the commercial extrusion processing of thermoplastics emits both particles and volatile organic compounds (VOCs) (Adams et al 1999), and some of the thermal decomposition products are recognized to be toxic (Rutkowski and Levin 1986;Unwin et al 2013;Yoon et al 2010). It follows that FDM 3D printers are potentially hazardous to operate in certain indoor environments.…”
Section: Introductionmentioning
confidence: 99%
“…While interpreting these outcomes, it seems reasonable to assume that increased activities of antioxidant enzymes might be indicative of increased oxidative stress, possibly caused by an occupational exposure of nail technicians. Indeed, exacerbation of oxidative stress has already been implicated in mechanisms underlying the effects exerted by the low-level exposure to VOC in both the animal models (22,45) and human subjects (10,11,46). Notwithstanding, the above-mentioned lack of any significant changes in levels of TBARS and DNA strand breaks between nail technicians and control subjects seems to contradict this thesis.…”
Section: Grešner Et Almentioning
confidence: 42%